The Effect of Product Quality, Price and Personal Selling on Customer Satisfaction and Loyalty of Herbalife Customers - Suharyono; Novi Pahlamalidie (HM Publisher, 2021)
This research was aimed to analyse the effect of product quality, price, personal selling to customer satisfaction and loyalty. The participant of this study was 125 people. Data were collected by questionnaires and structural equation model (SEM) were applies as an analysis technique. The results analysis showed that product quality, price, personal selling have positive and significant effect on the customer satisfaction and customer loyalty. The implication is product quality, price, personal selling need to be increased in order to customer satisfaction and customer loyalty.